Inclusive J/[psi] production at mid-rapidity in pp collisions at s√ = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Journal of high energy physics, 2019)
Inclusive J/ψ production is studied in minimum-bias proton-proton collisions at a centre-of-mass energy of s√ = 5.02 TeV by ALICE at the CERN LHC. The measurement is performed at mid-rapidity (|y| < 0.9) in the dielectron decay channel down to zero transverse momentum pT, using a data sample corresponding to an integrated luminosity of Lint = 19.4 ± 0.4 nb−1. The measured pT-integrated inclusive J/ψ production cross sec- tion is dσ/dy = 5.64 ± 0.22(stat.) ± 0.33(syst.) ± 0.12(lumi.) μb. The pT-differential cross section d2σ/dpTdy is measured in the pT range 0–10 GeV/c and compared with state-of- the-art QCD calculations. The J/ψ 〈pT〉 and ⟨p2T⟩ are extracted and compared with results obtained at other collision energies.